GENDER INEQUALITY IN THE WORKPLACE: AN INTERNATIONAL LAW ANALYSIS OF THE PROTECTION OF WOMEN WORKERS' HUMAN RIGHTS - Raesitha Zildjianda; Biyes Nurul Atika; Santriana (ASIAN PUBLISHER, 2025)
Gender inequality in the workplace remains a serious issue in the context of human rights. Women often face discrimination in the form of wage disparities, limited access to leadership positions, and insufficient protection of maternity and reproductive rights. This situation reflects violations of the principles of equality and non-discrimination as guaranteed by international legal instruments. This study aims to examine the protection of women workers' rights under international law and to analyze the challenges of its implementation in various countries. The research employs a qualitative method with a literature study approach, analyzing international legal documents, including the Universal Declaration of Human Rights (UDHR), the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW), and conventions of the International Labor Organization (ILO). A comparative approach is also applied to assess the effectiveness of these legal standards at the national level. The findings indicate that although international law provides a comprehensive framework of protection, including the principles of non-discrimination, equal pay, maternity leave rights, and protection from workplace violence, its implementation remains constrained. Key obstacles include differences in national regulations, entrenched patriarchal culture, weak law enforcement, and the low awareness of women workers regarding their rights. Therefore, harmonizing national rules with international standards, strengthening monitoring mechanisms, implementing gender-responsive public policies, and enhancing education for women workers are necessary to ensure more effective protection of human rights.